We're going on a bear hunt - Rosen, Michael; Oxenbury, Helen (Walker Books London, 2014)
For brave hunters and bear-lovers, this is the classic chant-aloud by Michael Rosen and Helen Oxenbury in a beautiful 25th-anniversary edition. We're going on a bear hunt. We're going to catch a big one. Will you come too? For a quarter of a century, readers have been swishy-swashying and splash-sploshing through this award-winning favourite. Follow and join in the family's excitement as they wade through the grass, splash through the river and squelch through the mud in search of a bear. What a surprise awaits them in the cave on the other side of the dark forest! It was the winner of the 1989 Smarties Book Prize and highly commended for the Kate Greenaway Medal. This anniversary edition is a jacketed paperback - embellished with gold foil, gold bear logos and a special gold sticker